Pengamanan dan Penyelamatan Arsip Statis di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Putri, Rahmi Fetika; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractThe writing of this paper aims to discuss Static Archive Security and Rescue in the Archives and Library Services of Sumatra Province. This study aims to; (1) Describe the security of static archives in the Department of Archives and Library of West Sumatra Province. (2) Describe the static archive rescue at the West Sumatra Province Archives and Library Service. (3) Describe the obstacles to static safety and rescue in the Department of Archives and Library of West Sumatra Province. (4) Describe efforts in static safety and rescue in the Department of Archives and Library of West Sumatra Province. The method used is descriptive method. Data was collected through observation and direct interviews with officers in the Archives and Library Service of West SumatraProvince. Based on the results of the research, Static Archive Safety and Rescue in the Archives and Library Service of West Sumatra Province are as follows: First, physical security and rescue of archives in the Archives and Library Service of West Sumatra Province is carried out lamination process, fumigation regulates moisture/dryness and air temperature room. In order to secure and record static archives in terms of information, it can be done by controlling every person who will access the static archive must go through a predetermined procedure, store static files in a special room that is maintained. The two constraints faced in securing and rescuing the static archive of the Archives and Libraries of West Sumatra Province are the lack of human resources in securing and holding static archives, the lack of adequate infrastructure for securing and rescuing static archives and lack of awareness of Opd and Skpd to report archives static to the Archives and Library Service of West Sumatra Province.The three efforts made to overcome the obstacles faced in securing and saving the static archive of the Archives and Library Service of West Sumatra Province by providing training programs and apprenticeship staff to national archives. Then complete and maintain facilities and infrastructure to secure and record static archives and send letters to OPD and SKPD to submit static files to them to the Archives and Libraries of West Sumatra Province.Keyword:Â static archive of the Archives and Library Service of West Sumatra Province